A Study of Theory on Algebra Graphs on Group D2n, Sn and An Group: Exploring the Role of Algebra and Graphs in Different Disciplines (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Algebra is one of the main areas of pure mathematics that uses mathematical statements such as term, equations, or expressions to relate relationships between objects that change over time. Algebra is used in finance, engineering and numerous fields of science. It is actually very common to perform simple algebra without realizing it for an average person. If you've got 20 rupees for two rupee candy bars, for example, to go into a store. This shows us the 2x = 10 equation, where x is the number of sweets you can buy. Many people don't know that the Algebra is such a calculation they do it only. Algebra is needed in your everyday life whether you like it or not. The role of the history of mathematics in improving the learning of mathematics has increased in recent years. Educators worldwide have developed and carried out research on the use of mathematical history in mathematical education. Certain results of this study were reported in meetings and in papers in different journals of interested organisations. A research programme, with contributions from many parts of the world, starts to emerge. This program includes a consolidated and critical bibliography of work done and a program that provides an understanding of the factors involved in the relationship between the history and educational sciences of mathematics, in various fields of mathematics, with students and pupils at various levels and with different backgrounds and environments. The aim is also to identify and distribute information and good practice in situations of learning and teaching.